Portugal - Simões, Teresa (2013)
Due to its location, Portugal has several valuable renewable resources for electricity production. It has a high level of solar radiation, moderate wind resource, and considerable vegetable and animal biomass potential. Ocean and hydro resources are also present, mainly the latter—although its major development took place in 2006 with the construction of large hydraulic power stations. Wave energy systems are now under development; the PELAMIS project, the first of its kind, is installed and has been functioning since the beginning of 2008. Nevertheless, Portugal still depends greatly on foreign countries for oil, gas, and coal resources, but it is taking large steps toward sustainable renewables-based electricity generation. Government and competent authorities established several measures in recent years that created incentives to install renewable energy systems and created the conditions for economic development in the energy sector. Regarding renewable energy systems, at the end of 2008 Portugal had about 8,151 MW capacity (1), corresponding to an estimated energy production of about 23,179 GWh. This production constitutes 43.3% of national electricity demand. However, this represents a 9% decrease in production compared with 2007, largely due to the decrease hydropower production. The goals defined for 2010 and 2013—that 39% and 45%, respectively, of the national electricity demand be generated from RES—are within reach. Wind generation at the end of 2008 was about 11% of the total national electrical demand—50.6 TWh (2). Also, use of renewable sources for micro generation of electricity is growing and as a result of legislation published at the end of 2007 (Dec. Law 363-2007, 2 November). The public in general has responded in large numbers to the initiatives and the programs that followed. By the end of 2008, 5,768 license requests had already been granted and registered on the web site of CERTIEL (3), the governing agency, corresponding to 19,772 kW of capacity. Of these registered systems, 7,137 kW are ready for inspection and about to start production (4).